Tingkat Persepsi Pekebun Terhadap Agroforestri Berbasis Kelapa Sawit di Kecamatan Galang Kabupaten Deli Serdang Provinsi Sumatera Utara - Zannah, Adelia; Wahyudi, Dedi; Yusuf, Mukhtar (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Deforestation has become a major environmental concern due to widespread land clearing. Diversification of crops is important as a solution to the problems of deforestation and monoculture farming systems through agroforestry. Agroforestry combines forestry with plantation crops to increase land productivity, ecosystem balance, food security, and human welfare. This study aims to examine the level of perception of farmers towards palm oil-based agroforestry in Galang District, Deli Serdang Regency, North Sumatra Province. The study location is in Galang District, Deli Serdang Regency, North Sumatra. Samples were taken from six villages in Galang District. This study was conducted from March to May 2025. The methodology used was quantitative descriptive. Data were collected through questionnaires, interviews, and observations. The level of perception was measured using a Likert scale. The data analysis used in this study was descriptive analysis with a continuous Likert scale. This scale had a minimum value of 1 and a maximum value of 5, with a total of 68 respondents. The farmers' perceptions were analyzed based on two main indicators, namely acceptance and evaluation. The results of the study showed that farmers' perceptions of oil palm-based agroforestry were in the low group, namely 46% of the total.